A compact MIMO multiband antenna for 5G/WLAN/WIFI-6 devices - Zakaria, Zahriladha; Al Gburi, Ahmed Jamal Abdullah; Ali, Ayyaz; Munir, Mehr E; Marey, Mohamed; Mostafa, Hala; Bhatti, Farooq Ahmed (MDPI AG, 2023)
This research work presents a compact design of a Multiple-Input Multiple-Output (MIMO) multiband antenna along with high-isolation characteristics. The presented antenna was designed for 3.50 GHz, 5.50 GHz, and 6.50 GHz frequencies for 5G cellular, 5G WiFi, and WiFi-6, respectively. The fabrication of the aforementioned design was undertaken using FR-4 (1.6 mm thickness) substrate material with a loss tangent and relative permittivity of about 0.025 and 4.30, respectively. The two-element MIMO multiband antenna was miniaturized to 16 × 28 × 1.6 mm3, making it desirable for devices operating in 5G bands. High isolation (>15 dB) was attained with thorough testing without employing a decoupling scheme in the design. Laboratory measurements resulted in a peak gain of 3.49 dBi and an efficiency of around 80% in the entire operating band. The evaluation of the presented MIMO multiband antenna was carried out in terms of the envelope correlation coefficient (ECC), diversity gain (DG), total active reflection coefficient (TARC), and Channel Capacity Loss (CCL). The measured ECC was less than 0.04, and the DG was well above 9.50. The observed TARC was also lower than −10 dB, and the CCL was below 0.4 bits/s/Hz in the entire operating band. The presented MIMO multiband antenna was analyzed and simulated using CST Studio Suite 2020.